The D1CT‐7 mouse model of Tourette syndrome displays sensorimotor gating deficits in response to spatial confinement - Godar, Sean C (Br J Pharmacol, 2015)
BACKGROUND AND PURPOSE: The D1CT‐7 mouse is one of the best known animal models of Tourette syndrome (TS), featuring spontaneous tic‐like behaviours sensitive to standard TS therapies; these characteristics ensure a high face and predictive validity of this model, yet its construct validity remains elusive. To address this issue, we studied the responses of D1CT‐7 mice to two critical components of TS pathophysiology: the exacerbation of tic‐like behaviours in response to stress and the presence of sensorimotor gating deficits, which are thought to reflect the perceptual alterations causing the tics. EXPERIMENTAL APPROACH: D1CT‐7 and wild‐type (WT) littermates were subjected to a 20 min session of spatial confinement (SC) within an inescapable, 10 cm wide cylindrical enclosure. Changes in plasma corticosterone levels, tic‐like behaviours and other spontaneous responses were measured. SC‐exposed mice were also tested for the prepulse inhibition (PPI) of the startle response (a sensorimotor gating index) and other TS‐related behaviours, including open‐field locomotion, novel object exploration and social interaction and compared with non‐confined counterparts. KEY RESULTS: SC produced a marked increase in corticosterone concentrations in both D1CT‐7 and WT mice. In D1CT‐7, but not WT mice, SC exacerbated tic‐like and digging behaviours, and triggered PPI deficits and aggressive responses. Conversely, SC did not modify locomotor activity or novel object exploration in D1CT‐7 mice. Both tic‐like behaviours and PPI impairments in SC‐exposed D1CT‐7 mice were inhibited by standard TS therapies and D(1) dopamine receptor antagonism. CONCLUSIONS AND IMPLICATIONS: These findings collectively support the translational and construct validity of D1CT‐7 mice with respect to TS. LINKED ARTICLES: This article is part of a themed section on Updating Neuropathology and Neuropharmacology of Monoaminergic Systems. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v173.13/issuetoc